Genotypic Shift and Diversification of MRSA Blood Stream Isolates in a University Hospital Setting: Evidence from a 12-Year Observational Study - Yuka Motomura; Motoyasu Miyazaki; Mitsuhiro Kamada; Shinichi Morimoto; Yoshihiko Nakamura; Tomomitsu Satho; Tohru Takata; Nobuhiro Kashige (Antibiotics, 2024)
There have been few reports regarding the long-term trends in the genotypes of methicillin-resistant Staphylococcus aureus (MRSA) bloodstream isolates. Therefore, this study was performed to investigate the longitudinal trends in the genotypes of MRSA bloodstream isolates obtained from hospitalized patients during a 12-year study period from 2010 to 2021 at a tertiary care university hospital. Over the 12-year period from 2010 to 2021, we conducted a genetic investigation focusing on 245 MRSA strains isolated from the blood of hospitalized patients. The genotypes of the MRSA bloodstream isolates were determined by Staphylococcal Cassette Chromosome mec (SCCmec) typing, accessory gene regulator (agr) typing, PCR-based ORF typing (POT), and multilocus sequence typing (MLST). Strains with the same POT type detected in two or more isolates were designated as epidemic clones, while strains without a common POT type were classified as sporadic clones. Until 2015, isolates with SCCmec II/agr II were prevalent, but isolates with SCCmec IV/agr III increased from 2016. A total of 128 strains (52%) were identified as epidemic clones, while 117 strains (48%) were classified as sporadic clones. The detection rate of sporadic clones increased significantly since 2016 (p < 0.05). The epidemic clones were classified into three clusters, with MRSA of clonal complex (CC) 1 being prominent after 2016. This study showed that the genotypes of MRSA bloodstream isolates underwent a shift from SCCmec II/agr II type to SCCmec IV/agr III type, with a notable increase in MRSA of CC1, after 2016. There was a significant increase in the proportion of sporadic strains among the isolates, suggesting the diversification of genotypes.